Air Travel for Subjects Receiving Long-Term Oxygen Therapy - Campbell, Christina D; Smyth, Matthew W; Brown, Lindsay; Kelly, Emer (Respiratory care, 2018)
Ambulatory oxygen (O ) is the recommended treatment for hypoxemia at rest or induced by exercise. Commercial aircraft often fly at altitudes of 30,000 feet; their cabins are pressurized to altitudes of 6,000-8,000 feet, with an equivalent F of 0.15. O supplementation, for those receiving baseline ambulatory O , is paramount. We gathered information on subjects' experience traveling with supplementary oxygen and reasons individuals receiving O do not travel. Subjects were identified using a home oxygen database. Data were gathered by postal questionnaire. The objective of this study was to gather information relevant to subjects' experience organizing travel with supplementary oxygen and their experience of traveling itself. Between 2013 and 2015, 512 patients were entered into the database: 277 were excluded (269 had died, 8 had incomplete records). We sent 235 questionnaires, and 50 responses were received (21% response rate). Of these, 11 (22%) were returned as the patient had died, 20 (40%) had not traveled by air, 11 (22%) had flown with O , 4 (8%) no longer used O , and 4 (8%) forms were incomplete. Of those who traveled with O , 54% found it complicated to organize their trip, 72% found it complicated to access information, and 81% would fly again. Regarding those who had never flown with O , 35% were unaware that O was available on commercial aircraft, 30% had no wish to travel, and 30% had worries regarding their health. Air travel is challenging; however, those who did travel reported a mainly positive experience. Increasing available information on options for travel should help individuals.